Photocatalytic activity of Fe doped ZnS nanoparticles and carrier mediated ferromagnetism. Issue 3 (September 2015) - Dixit, Namrata; Vaghasia, Jayraj V.; Soni, Saurabh S.; Sarkar, Mitesh; Chavda, Mukesh; Agrawal, Naveen; Soni, Hemant P.
Graphical abstract: Highlights: Both direct as well as OH mediated degradation of dye pollutant is achieved. The BET analysis reveals that the material is mesoporous. Maximum surface stabilization (−31.02 mV) is achieved with 5.0% Fe doping. Photocatalytic performance was evaluated spectrophotometrically using RhB solution. Uniform distribution of Fe 2+ or Fe 3+ dopant ions in the ZnS host, manifests charge mediated ferromagnetism. Abstract: ZnS nanoparticles (ZnS NPs) with different amount of Fe as dopant ions had been synthesized. X-ray diffraction (XRD) and energy dispersive X-ray (EDX) analysis were carried out for particle size, phase and elemental analyses. Transmission electron microscopy (TEM) was employed for morphological studies. Defect chemistry and the photo-processes occurring in the material were understood by using UV–vis absorption and photoluminescence (PL) spectroscopy. The synthesized nanoparticles were evaluated as photocatalyst for the degradation of rhodamine B (RhB) dye in an aqueous solution illuminated by high pressure mercury vapour (HPMV) lamp at RT. In this study, we have shown that architecture of the photocatalyst is important to achieve optimum performance. By Mössbauer spectroscopy and vibrating sample magnetometry (VSM), it has been established that not only the locations of the dopant but also their oxidation states are critical for charge carrier dynamics. Charge carriers can be trapped and directed towards the adsorbed dye molecules by changing the oxidation state of the dopant Fe ions. On the basis of electrochemical analyses (cyclic voltammetry, Mott–Schottky plots and electrochemical impedance spectroscopy) it has been shown that dopant increases the level of charge carriers (electrons) in the material responsible for ferromagnetism at RT. Efficient catalytic recovery can be achieved if the photocatalytic material possesses ferromagnetic property.